Pengaruh Obligasi Syariah (Sukuk), Reksadana Syariah, dan Saham Syariah Terhadap Pertumbuhan Ekonomi di Indonesia Tahun 2015 – 2020 - Novita Cahyani Wiyati Putri; Deny Yudiantoro (Ekonomis: Journal of Economics and Business, 2023)
The purpose of this study was to examine and investigate the effect of Islamic bonds (sukuk), Islamic mutual funds, and Islamic stocks on economic growth in Indonesia in 2015 - 2020. The approach used in this research is quantitative with associative research. The population in this research study consisted of data obtained from the OJK website www.ojk.go.id and BPS www.bps.go.id. The sample consists of published statistical data for the years 2015 - 2020 and uses multiple linear analysis techniques. The results of the study are: 1) sharia bonds have a positive and significant effect on economic growth in Indonesia 2) sharia mutual funds have a positive and significant effect on economic growth in Indonesia 3) sharia stocks have a negative and insignificant effect on economic growth in Indonesia 4) together - the same as sharia bonds, sharia mutual funds, and sharia stocks have a positive and significant effect on economic growth in Indonesia.